Free-living nematodes from the deep-sea Håkon Mosby Mud Volcano, including the description of two new and three known species - Portnova, Daria (Zootaxa, 2009)
Two new and three known species of the genera Aponema Jensen, 1978, Molgolaimus Ditlevsen, 1921, Sabatieria Rouville, 1903, and Terschellingia De Mann, 1888 were found at the deep-sea Håkon Mosby Mud Volcano, at a depth of 1250m, in the Norwegian Sea. Aponema ninae sp. n. is characterized by short body length, short spicules, gubernaculum with wide apophyses, which are bevelled on the top, and long narrowed tail with drop-shape thickened tip and caudal setae. The new species most resembles Aponema torosa (Lorenzen, 1973). Molgolaimus haakonmosbiensis sp. n. differs from all other species of Molgolaimus by shape and length of spicules; relations of spicule length to the anal body diameter; presence of two supplements. Spicules of the new species are short (30.5 µm), slender, twisted with amplate and excurved proximal parts. The appearance of our specimen of Sabatieria ornata fits well with the original description of Ditlevsen, 1918. Specimens of Terschellingia distlamphida Juario, 1974 also fit the original description based on nematodes sampled from the sub littoral of the German Bight. However, the Norwegian specimens have a shorter (1010 µ m vs. 1343 µ m) and thicker body (a=64.6 µ m vs. a=32.0 µm). The Håkon Mosby specimens of Terschellingia longicaudata De Mann, 1907 differ from the original description in body length and thickness: 1094 µm vs. 1429 µm, and a=22.3 µm vs. 49.0 µm correspondingly, but agree with descriptions by other authors, especially with the one by Chitwood (1951).